1975
DOI: 10.1037/0096-1523.1.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Aging faces as viscal-elastic events: Implications for a theory of nonrigid shape perception.

Abstract: A theory for the perception of events is proposed using the concepts of transformational and structural invariants. This approach involves the application of a method of spatial coordinate transformation to characterize the remodeling of faces by growth. By construing growing faces to the viscal-elastic events, the perception of the relative age level faces in made amenable to the proposed event perception analysis. Shear and strain transformation are compared as alternative formulations of growth-produced cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
0
2

Year Published

1977
1977
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 1 publication
(3 reference statements)
4
127
0
2
Order By: Relevance
“…This is consistent with previous research demonstrating the effects of similar transformations on apparent age (eg Pittenger and Shaw 1975;Mark and Todd 1983;Bruce et al 1991), although the effects of the strain transformation in our experiments were weaker than the results of previous research might have led us to expect. One reason for this is that in experiment 2 we used a between-subjects design, which may have been less sensitive to the effects of strain than the within-subjects designs typically used by previous researchers to investigate this phenomenon.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous research demonstrating the effects of similar transformations on apparent age (eg Pittenger and Shaw 1975;Mark and Todd 1983;Bruce et al 1991), although the effects of the strain transformation in our experiments were weaker than the results of previous research might have led us to expect. One reason for this is that in experiment 2 we used a between-subjects design, which may have been less sensitive to the effects of strain than the within-subjects designs typically used by previous researchers to investigate this phenomenon.…”
Section: Discussionsupporting
confidence: 93%
“…Through growth and ageing the face comes to occupy a larger part of the head, and the internal features (eyes, nose, and mouth) effectively move upwards on the head. During the past twenty years numerous studies have demonstrated that manipulations of the level of cardioidal strain applied to a face affect subjects' judgments of the age of the face (eg Pittenger and Shaw 1975;Pittenger et al 1979;Todd 1983, 1985;Bruce etal 1989). Faces appear older if the strain transformation is applied in one direction, and younger if it is applied in the opposite direction.…”
Section: Introductionmentioning
confidence: 99%
“…As noted in the introduction, the affordance structure of an event is composed of a component that remains constant and a component that changes (Pittenger & Shaw, 1975). The transformable displays in this experiment contain geometric information which specifies a single object undergoing a certain change-the affordance structure of a certain unified event.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, biomorphic transformations of nonrigid objects (such as growth, flexion, and locomotion) may require excursions into topology to locate their defining invariants (see Pittenger & Shaw, 1975 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation